1999
DOI: 10.1016/s0954-6111(99)90007-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of the expiratory phase in obstructive sleep apnoea

Abstract: The role of the expiratory phase in obstructive sleep apnoea (OSA) is not well known. The aim of our study was to verify the contribution of expiratory narrowing to apnoea in a group of OSA patients by evaluating the effects of short-term treatment with continuous positive airway pressure (CPAP), intermittent positive pressure ventilation (IPPV) and bi-level positive airway pressure (BIPAP). We studied a selected group of 10 OSA patients whose therapeutic pressure level of CPAP was at least 10 cm H2O. During C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A distinctive observation in this ASV study pinpointed the ubiquitous inability of chronic insomnia disorder patients with comorbid OSA/UARS to adapt to standard PAP devices, such as continuous positive airway pressure (CPAP), continuous positive airway pressure with expiratory pressure relief (CFLEX), automatic continuous positive airway pressure (APAP), and Bilevel positive airway pressure (BPAP) due to self-reported discomfort and intolerance triggered by the vaguely defined phenomenon of expiratory pressure intolerance (EPI)41,42 even among those using PAP devices with basic expiratory pressure relief (EPR) systems 39. These adverse effects resolved with ASV use,43 and in our clinical experience, many insomnia patients also adapt well to autobilevel PAP (ABPAP) devices 43,44.…”
Section: Introductionmentioning
confidence: 99%
“…A distinctive observation in this ASV study pinpointed the ubiquitous inability of chronic insomnia disorder patients with comorbid OSA/UARS to adapt to standard PAP devices, such as continuous positive airway pressure (CPAP), continuous positive airway pressure with expiratory pressure relief (CFLEX), automatic continuous positive airway pressure (APAP), and Bilevel positive airway pressure (BPAP) due to self-reported discomfort and intolerance triggered by the vaguely defined phenomenon of expiratory pressure intolerance (EPI)41,42 even among those using PAP devices with basic expiratory pressure relief (EPR) systems 39. These adverse effects resolved with ASV use,43 and in our clinical experience, many insomnia patients also adapt well to autobilevel PAP (ABPAP) devices 43,44.…”
Section: Introductionmentioning
confidence: 99%
“…Distinguishing between inspiratory and expiratory sound events will allow better estimation of breathing patterns. Moreover, several studies have found that expiratory events may hold hidden information for SDB diagnosis [9][10][11]. Thus, by using the additional expiratory information, SDB diagnosis and sleep quality assessment can be improved [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Forty million people nationwide are diagnosed with a sleep disorder; the most serious is obstructive sleep apnea (OSA). It is estimated that 10% to 15% of the population is affected by OSA 1–3 …”
mentioning
confidence: 99%
“…It is estimated that 10% to 15% of the population is affected by OSA. [1][2][3] The most common complaint is snoring. This symptom is not of frivolous importance.…”
mentioning
confidence: 99%